Mathematical operation and symbol notation
 Statements
P < Q > T,
R ≥ Q.
Conclusions
I. R > P
II. T < R

View Hint View Answer Discuss in Forum
Given that,
P < Q > T ...................(i)
R ≥ Q ......................(ii)
On combining the statements (i) and (ii), we get
P < Q ≤ R
R ≥ Q > T
Conclusions
I. R > P
II. T < RCorrect Option: E
Given that,
P < Q > T ...................(i)
R ≥ Q ......................(ii)
On combining the statements (i) and (ii), we get
P < Q ≤ R
R ≥ Q > T
Conclusions
I. R > P ...... (true)
II. T < R .......(true)
So, it is clear that both Conclusions I and II are true.
 Which one of the four interchange in signs or numbers would make the given equation correct ?
6 x 4 + 2 = 16

View Hint View Answer Discuss in Forum
Apply all option one by one.
Correct Option: C
Apply all option one by one.
∵ 6 x 4 + 2 = 16 ⇒ 4 + 6 x 2 = 16 ⇒ 4 + 12 = 16
 Statements
A = B ≤ C,
A > R
Conclusions
I. B > R
II. R < C

View Hint View Answer Discuss in Forum
Given that,
A = B ≤ C ................(i)
A > R .........................(II)
On combining the statements (i) and (ii), we get
R < A = B ≤ C
Conclusion
I. B > R. .................(true)
II. R < C .................(true)Correct Option: E
Given that,
A = B ≤ C ................(i)
A > R .........................(II)
On combining the statements (i) and (ii), we get
R < A = B ≤ C
Conclusion
I. B > R. .................(true)
II. R < C .................(true)
So, it is clear that both Conclusions I and II follow from the given statements.
 Statements
S > C ≥ 0, P < C
Conclusions
I. 0 < P
II. S > P

View Hint View Answer Discuss in Forum
Given that
S > C ≥ O ....(i)
P < C ...............(ii)
On combined the statement (i) and (ii), we get
S > C > P
P < C ≥ O
Conclusions
I. O < P............... (false)
II. S > P ................ (true)Correct Option: A
Given that
S > C ≥ O ....(i)
P < C ...............(ii)
On combined the statement (i) and (ii), we get
S > C > P
P < C ≥ O
Conclusions
I. O < P............... (false)
II. S > P ................ (true)
So, it is clear that only Conclusion II follow from the given statements.
 Statements
H ≥ I = J > K ≤ L
Conclusions
I. K < H
II. L ≥ I

View Hint View Answer Discuss in Forum
Given that,
H ≥ I = J > K ≤ L
Here, statements are already combined
H ? I = J > K means H > K
Conclusions
I. K < H (true)
II. L ≥ I (false)Correct Option: A
Given that,
H ≥ I = J > K ≤ L
Here, statements are already combined
H ? I = J > K means H > K
Conclusions
I. K < H (true)
II. L ≥ I (false)
So, it is clear that only Conclusion I follows from the given statements.